Analysis of the Reading Guide-Based Physics Practicum Instruction Model to Improve Students' Creative Thinking Ability - Rena Herdiana; Yanti Sofi Makiyah; Nana Nana; Dwi Sulistyaningsih (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2021)
This research aims to examine the use of reading guide-based physics practicum manuals to improve students' creative thinking skills. The type of research method used in this research is a literature study. Data collection is obtained from various journals, books, and proceedings that are relevant to the focus of the research and based on creative thinking indicators, namely fluency, flexibility, originality, and elaboration in a reading guide-based practical model. The data were analyzed by the correlation between the indicators of creative thinking ability and the practicum guide model used. The results of this research are a collection of references that are relevant to the focus of the research. Based on the results of the literature study, it was found that there was a correlation or continuity between the criteria for reading guide learning strategies and indicators of creative thinking skills, namely: 1) Fluency, 2) flexibility, 3) originality, and 4) elaboration. Therefore, it is concluded that the use of variations of the reading guide-based physics practicum model will be able to improve students' creative thinking skills if it is used in learning that carries out physics practicum.